The strategic role of supply chain management in the luxury fashion sector - Brugger, Gernot (2020)
This thesis examines how supply chains within the luxury fashion sector impact the business performance of luxury fashion brands. Hence, this thesis is going to examine two case study examples of companies that have undergone strategic changes regarding their supply chain strategy. In particular, the emphasis of the analysis will lie on the impact that supply networks and distribution channels have on the performance of the discussed luxury fashion brands. Our findings suggest that both examined cases successfully adapted their supply chain strategy in order to improve business performance. This implies that core elements of supply chain management can have a significant impact on business performance. Moreover, our findings show that the sample companies adapted their supply chain strategy across three main dimensions (sourcing, production, and distribution). Companies reversed their production and manufacturing strategy from outsourcing back to insourcing. By providing insight on how a luxury fashion brand can improve its performance by adapting its supply chain strategy, our study enriches the understating of the luxury fashion sector. In addition, our research adds value to existing literature on supply chain management in the luxury fashion sector.